The Effect of Good Corporate Governance, Firm Size, Leverage, and Firm Performance on Earnings Management: Entrenchment Management as a Moderation Variable - Taufiq Dwi Saputra; Zulfikar Zulfikar (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2023)
This study aims to examine the effect of good corporate governance mechanisms which include the board of commissioners, board of directors, audit committee, firm size, leverage, and firm performance on earnings management with management entrenchment as a moderating variable. This type of research uses quantitative methods. The sampling technique in this study used a purposive sampling method based on predetermined criteria, obtained as many as 68 sample data from 17 sample companies in real estate and property companies listed on the Indonesia Stock Exchange (IDX) for 4 years in the 2018-2021 period. The results of this study indicate that the good corporate governance variable with the proxy of the board of directors has a negative effect on earnings management, the leverage variable has an effect on earnings management. Meanwhile, the good corporate governance variable by proxies for the board of commissioners, audit committee, firm size, and firm performance has no effect on earnings management. Management entrenchment has no effect on the interaction of leverage with earnings management, the interaction between firm performance and earnings management. Management entrenchment strengthens the influence of good corporate governance by proxies for the board of commissioners, board of directors, audit committee, and firm size on earnings management.